Meta-Analysis of Obstacles to the Establishment of Succession - Marzieh Abdul Rezaei; Hamid Rezaiefar; Mohammad Mohammadi; Hosien Hakimpur (مدیریت بهره وری)
Today, the management of various organizations during succession process results in identifying the talents, abilities, and interests of employees within the organization or people outside the organization, which increases the productivity of the organization. Hence, the purpose of the present research is a meta-analysis of the obstacles to the establishment of succession. The research method is a quantitative systematic review in which the seven-step method of Sandelowski and Barroso (2007) was used. The reviewed sources were the scientific information of academic Jahad, Scopus, Emerald, Science Direct, and Springer, including 124 articles related to the keywords of the research. After searching the research topic, the abstracts of 74 articles were reviewed, of which 22 articles were removed, and 52 articles entered the next stage to be reviewed in full text. Finally, 22 articles were found to be unrelated to the text and were removed, and 30 articles were selected to be analyzed. The findings of the research include 84 indicators or variables, which include individual barriers, organizational barriers, managerial barriers, occupational barriers, human resource barriers, and succession implementation barriers. The findings of the research have shown that the lowest amount in the effect size is related to the barriers of immediate and avoidant decision-making style and the highest amount belongs to the effort to maintain the existing status.